Intra-company and strategic planning tools at industrial enterprises: Innovative solutions and developments - V. V. Lebedev (Управление)
Intra-company and strategic planning consider the organization from different sides, combining the results obtained to compile a comprehensive strategy based on planned indicators, based on the capabilities of the enterprise and the assessment of external competitive advantages. In addition, intra-company and strategic planning helps industrial enterprises to make rational decisions and control risks in a volatile business environment. At the output, the company receives a single plan with priority areas of business development. The purpose of the work is to analyze the use of intra-company and strategic planning tools at industrial enterprises. In the conducted research general scientific methods were used: analysis, synthesis, grouping, generalization. Project and process management becomes a solution in the implementation of the investment block of the business strategy (a key tool). In PJSC “Quadra” it was proposed to introduce a projectprocess approach to management. The modified life cycle management system of the investment project (within the framework of the project-process approach) will avoid the following losses: in the form of RUB 250 thousand of the working time fund of the engineering staff of the branch. Rosatom State corporation considered a Scrum methodology, where social and economic effect from its application is 70% of successfully realized tasks, 20% – experience exchange between employees, 10% – training development.